Potensi Tumbuhan Etnofarmasi dengan Pendekatan Nilai Guna Spesies di Kawasan Sumberbrantas Batu Jawa Timur - Muhammad Ainur Rosyid Ridho; Indah Trisnawati; Kristanti Indah Purwani (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Indonesia is recognized as a country with high biodiversity, particularly in terms of flora and fauna, with approximately 17% of the world’s total species found within its borders. One of the most significant aspects of this biodiversity is the presence of medicinal plants, which have been traditionally used by Indonesian communities to treat various diseases, especially chronic and degenerative illnesses. Previous studies conducted in Indonesia have identified 65 species of medicinal plants from 38 different families, with a large proportion belonging to the Zingiberaceae (12.3%), Euphorbiaceae (7.6%), and Poaceae families. Most of these plants are sourced from forests, and Indonesian communities primarily use their leaves for herbal medicine. These traditional herbal remedies have been reported to treat 38 different diseases (Meliki & Lovadi, 2013). This study identifies 22 species of medicinal plants utilized by the residents of Sumberbrantas Village, who possess ancestral knowledge regarding their use. The research employed semi-structured interviews with 70 respondents, selected using the Snowball Sampling technique. The findings reveal that the following plants are commonly used: Allium sativum (Garlic), Amaranthus blitum (Slender amaranth), Annona muricata (Soursop), Apium graveolens (Celery), Beta vulgaris (Sugar beet), Coleus scutellarioides (Miana), Cosmos caudatus (Ulam raja), Curcuma longa (Turmeric), Cymbopogon citratus (Lemongrass), Ipomoea batatas (Sweet potato), Kaempferia galanga (Aromatic ginger), Mesona chinensis (Black grass jelly), Morinda citrifolia (Noni), Ocimum basilicum (Basil), Orthosiphon aristatus (Cat’s whiskers), Solanum tuberosum (Potato), Syzygium polyanthum (Indonesian bay leaf), Alpinia galanga (Greater galangal), Brassica oleracea (Broccoli), and Daucus carota (Carrot). Despite the increasing popularity of modern medicine, education and awareness regarding the benefits of medicinal plants should be emphasized to preserve local knowledge and promote awareness of traditional medicine’s potential. This study highlights the need for ethnobotanical documentation to support biodiversity conservation and the development of plant-based medicines in Indonesia.